2022
DOI: 10.1140/epjp/s13360-022-02865-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear data evaluation for decay heat analysis of spent nuclear fuel over 1–100 k year timescale

Abstract: Accurate nuclear data are essential in the evaluation of decay heat from spent nuclear fuel (SNF). The accuracy of such data was assessed using an approach that compares values reported in different evaluated libraries and determines whether discrepancies reflect inaccuracies in primary data. A short list of 43 isotopes which are most significant to SNF decay heat calculations over 1–100 k years was produced by combining generic reactor inventory code with decay heat analysis for undifferentiated SNF. Decay pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…All decay and in-growth calculations for the timespan between measurement date and EOL reference date make use of nuclear data. For consistency, users of the assay data should check whether their set of nuclear data correspond to the nuclear data used for the EOL calculations as different libraries may contain different nuclear data (Doran et al, 2022). Just to give an example: the half-life of Cm-244 in the ENDF/B-VIII.0 library (18.11 ± 0.03 years) is 0.6% higher than the one in the JEFF3.3 library (18.00 ± 0.10 years).…”
Section: Reporting Nuclear Datamentioning
confidence: 99%
“…All decay and in-growth calculations for the timespan between measurement date and EOL reference date make use of nuclear data. For consistency, users of the assay data should check whether their set of nuclear data correspond to the nuclear data used for the EOL calculations as different libraries may contain different nuclear data (Doran et al, 2022). Just to give an example: the half-life of Cm-244 in the ENDF/B-VIII.0 library (18.11 ± 0.03 years) is 0.6% higher than the one in the JEFF3.3 library (18.00 ± 0.10 years).…”
Section: Reporting Nuclear Datamentioning
confidence: 99%
“…This perspective conservatively assumes that the observed C/E spread is indicative of any future, possible variation between a calculated and real nuclide concentration, and that unaccounted sources of error exist. For example, in (Doran et al, 2022) it was concluded that the 137 Cs mean beta energies reported by JEFF3.3., and ENDF/ B-VIII.0 are in error. Also, newer evaluations of nuclear data do not necessarily lead to higher quality.…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
“…A maximum difference of almost 1.5% is noticed for the results obtained with JEFF-3.1.2. Differences in nuclear data relevant for the estimation of the decay heat of SNF between the main libraries (JEFF, ENDF/B) and recommended decay libraries (ENSDF, DDEP) are also discussed by Doran et al (2022). 4 Neutron detection system for SNF sample measurements…”
Section: Librarymentioning
confidence: 99%